Children’s peer relationships, well-being, and academic achievement: the mediating role of academic competence - Țepordei, Ana-Maria; Zancu, Alexandra S.; Diaconu-Gherasim, Loredana R.; Crumpei-Tanasă, Irina; Măirean, Cornelia; Sălăvăstru, Dorina; Labăr, Adrian V. (Frontiers in Psychology, 2023)
The present study aimed to explore the interplay among two indicators of children’s school peer relationships (i.e., peer acceptance and perceived number of friends) and two significant life domains (i.e., global life satisfaction and academic achievement). We also explored the potential mediating role of the perceived academic competence in these relations. Participants were 650 Romanian primary school students (45.7% boys), aged between 9 and 12 years old (Mage = 10.99). Path analysis showed a direct positive effect of perceived number of friends on children’s life satisfaction, as well as a direct positive effect of peer acceptance on academic achievement. Moreover, perceived academic competence mediated the links between each of the two indicators of peer relationships and children’s both life satisfaction and achievement. Several implications in the educational contexts are discussed.